The Financing Behaviour of the CEE Firms under the Impact of Financial Crisis: A Panel Regression Approach - Diana RUSU, Valentina; ROMAN, Angela (European Journal of Sustainable Development, 2018)
This paper studies empirical association between global financial shocks and firm behaviour towards liquidity needs across emerging countries from Central and Eastern Europe. Through this paper we aimed to identify the impact of the recent financial crisis on the financing decisions of the firms in seven Central and Eastern European countries (namely Bulgaria, Estonia, Latvia, Lithuania, Poland, Romania and Hungary). Using three multiple linear regression models, we wanted to observe the changes that appear in the use of various sources of financing as a result of the modification of five macroeconomic factors. The results obtained from the three multiple linear regression models show that in the context of the recent financial crisis, the financing decision of firms in the seven countries considered in the analysis was significantly influenced by the changes registered by four macroeconomic factors, respectively the interest rate on loans, the domestic credit granted to private sector, the inflation rate and the real GDP growth rate. Overall, our study highlights that the macroeconomic environment has a major impact on the financing behaviour of the firms. Keywords: capital structure, financing behaviour, macroeconomic factors, financial crisis, panel data